KOSAKATA TOPONIMI KOTA PANGKALPINANG - Lia Aprilia (Balai Bahasa Nusa Tenggara Barat, 2016)
This research focussed on vocabulary study relates to the name of place/region or toponimy of Pangkalpinang district. This study used descriptive method. The data collected through library study and field research in Pangkalpinang district. The result of this research can be described as: Nai Si Fuk or Star village, Semabung Village or Yung Fo Hin, Parit Lalang Village, White Coral Village or Sung Sa Tie, Salt Coral Village, Six Parit Village,Iron Village or Thiat Phu, Opas Village, Tangsi jail or prison, Gabek Village, Keramat Village,Seberang Village, Bukit Village,Bukit Tani Village, Bukit Baru Village, Bukit Nyatoh Village, Bukit Merapen Village, Sari Garden Village, Lo Ngin Buk Village,Tuatunu Village, Betur Village, Katak Village, Asam Village, Bacang Village, Kacangpedang Village, Ketapang Village, Ampui Village, Selindung Village, Bukit Intan Village, Bukit Besar Village, and Girimaya Village, Air Salemba Village, Sumberejo Village, Bogorejo Village, Terak Village, Rangkui Village, Pintu Air Village, Air Itam Village, Pasir Padi Village, Temberan Village, and Melintang Village.